1985
DOI: 10.1002/j.1460-2075.1985.tb04141.x
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of exon 1 from the c-myc gene results in prolonged c-myc mRNa stability.

Abstract: The human c-myc gene consists of three exons transcribed from two distinct promoters and the function of the first, noncoding exon is unknown. In COLO 320 cells, there co-exist normal and truncated (i.e., lacking exon 1) c-myc genes, both of which are transcribed. Studies on the turnover of c-myc mRNA show that the normal mRNA has an in vivo half-life of -30 min which is approximately similar to the turnover time of the mRNA in lymphoblastoid cells. However, the truncated mRNA was found to be substantially mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
1
2

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(85 citation statements)
references
References 39 publications
1
81
1
2
Order By: Relevance
“…This sequence is particularly noteworthy in light of the extremely high A+T content of noncoding regions in D. discoideum mRNAs (67). More definitive evidence for the importance of 5'-and 3'-UT regions has come from recent experiments in which these regions have been deleted, replaced, or transferred, resulting in substantial changes in the decay rates of individual mRNAs (22,42,53,64,74,76). The most well-characterized of the UT elements are the 3' AU-rich sequences associated with the GM-CSF mRNA (and other lymphokine and protooncogene mRNAs [12,50,74]) and the 3' stem-loop structure associated with the replication-dependent histone mRNAs (21,68 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence is particularly noteworthy in light of the extremely high A+T content of noncoding regions in D. discoideum mRNAs (67). More definitive evidence for the importance of 5'-and 3'-UT regions has come from recent experiments in which these regions have been deleted, replaced, or transferred, resulting in substantial changes in the decay rates of individual mRNAs (22,42,53,64,74,76). The most well-characterized of the UT elements are the 3' AU-rich sequences associated with the GM-CSF mRNA (and other lymphokine and protooncogene mRNAs [12,50,74]) and the 3' stem-loop structure associated with the replication-dependent histone mRNAs (21,68 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these complex decay kinetics reflect the sum of the decay rates of individual mRNAs (e.g., in D. discoideum, the most stable mRNAs have half-lives of approximately 10 h and the least stable mRNAs have half-lives which are approximately 10-fold shorter). It has been suggested that such large differences in the stability of individual mRNAs could be accounted for by differences in their respective sizes (39,52,58,63,78,81), poly(A) tail lengths (8,28,56,91), ribosome loading (1,26,33,41,45), or 5'-and 3'-untranslated (UT) sequences (42,53,64,69,74,76,89). To test the validity of these hypotheses, we have identified cloned cDNAs which encode mRNAs that are representative of the stability extremes in D. discoideum and have initiated a characterization of the properties of the respective mRNAs.…”
mentioning
confidence: 99%
“…Chicken c-mvc RNA can also potentially form a stem structure by annealing portions of exons 1 and 2 with a minimum free energy of AGO (250) of -45 kcal/mol (44) which is not as low as in the human RNA stem (-90 kcal/mol). More likely, removal of exon 1 affects RNA stability (15,34). Thus, the removal of exon 1 in most retrovirus-induced bursal lymphomas (11,37), as well as in the majority of c-myc-immunoglobulin locus translocations found in plasmacytomas (3,20,41,43) and some Burkitt's lymphomas (3,5), may enhance translation of c-myc (11,37).…”
Section: (40)mentioning
confidence: 99%
“…Due to translocation, the first untranslated exon of the normal c-myc mRNA is often replaced with other shorter 5' untranslated sequences (7). It has been demonstrated by several groups that this truncated c-myc mRNA has a longer half-life than normal full-length c-myc mRNA (13,32,34), suggesting that part of the signal for c-myc mRNA degradation may reside in exon 1. The increased stability of truncated c-myc transcripts contributes to the increased levels of c-myc transcripts which are probably casual in the malignant transformation of these B-cell tumors.…”
mentioning
confidence: 99%